Repetitive Blast Exposure Increases Appetitive Motivation and Behavioral Inflexibility in Male Mice - Baskin, Britahny; Lee, Suhjung Janet; Skillen, Emma; Wong, Katrina; Rau, Holly; Hendrickson, Rebecca C.; Pagulayan, Kathleen; Raskind, Murray A.; Peskind, Elaine R.; Phillips, Paul E. M.; Cook, David G.; Schindler, Abigail G. (Frontiers in Behavioral Neuroscience, 2021)
Blast exposure (via detonation of high explosives) represents a major potential trauma source for Servicemembers and Veterans, often resulting in mild traumatic brain injury (mTBI). Executive dysfunction (e.g., alterations in memory, deficits in mental flexibility, difficulty with adaptability) is commonly reported by Veterans with a history of blast-related mTBI, leading to impaired daily functioning and decreased quality of life, but underlying mechanisms are not fully understood and have not been well studied in animal models of blast. To investigate potential underlying behavioral mechanisms contributing to deficits in executive functioning post blast mTBI, here we examined how a history of repetitive blast exposure in male mice affects anxiety/compulsivity-like outcomes and appetitive goal-directed behavior using an established mouse model of blast mTBI. We hypothesized that repetitive blast exposure in male mice would result in anxiety/compulsivity-like outcomes and corresponding performance deficits in operant-based reward learning and behavioral flexibility paradigms. Instead, results demonstrate an increase in reward seeking and goal directed behavior and a congruent decrease in behavioral flexibility. We also report chronic adverse behavioral changes related to anxiety, compulsivity, and hyperarousal. In combination, these data suggest that potential deficits in executive function following blast mTBI are at least in part related to enhanced compulsivity/hyperreactivity and behavioral inflexibility and not simply due to a lack of motivation or inability to acquire task parameters, with important implications for subsequent diagnosis and treatment management.